Guidelines for the scale-up of an aqueous ceramic process: a case study of statistical process control - Mortara, L.; Alcock, Jeffrey R. (Cranfield University, 2011)
Process-scale up is the change from a feasibility study in a laboratory to a full-scale prototype production process. It is an important issue for the ceramics industry, but has been the subject of relatively little systematic research. This paper will show how certain manufacturing concepts used in a number of industries - can be applied to the scale up of a feasibility study level, aqueous tape casting process. In particular, it examines the elements of process standardisation using the example of the Statistical Process Control (SPC) technique applied to a sub process of an aqueous powder process. It illustrates that these elements are an essential step in moving from conceptual design to the process prototype.